2018
DOI: 10.1155/2018/9437815
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Experimental Study of Tribo-Mechanical Performance of Low-Temperature PVD Based TiN Coated PRCL Systems for Diesel Engine

Abstract: Piston ring and cylinder liner (PRCL) interface is a major contributor to the overall frictional and wear losses in an IC engine. Physical vapor deposition (PVD) based ceramic coatings on liners and rings are being investigated to address these issues. High temperature requirements for applications of conventional coating systems compromise the mechanical properties of the substrate materials. In the current study, experimental investigation of tribo-mechanical properties is conducted for various titanium nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Traditionally, it is considered that wear resistance of the coatings just depends on the hardness but nevertheless, elastic modulus also plays a vital contribution in the wear characteristics. [28]. The modulus of elasticity of the G17 piston ring is 110-140 GPa [29], whereas the modulus of elasticity at the complex chromium alloyed grey iron is 154-196 GPa according to DIN 1695 [27].…”
Section: Methodology Applied In Analysing the Chemical Composition Ofmentioning
confidence: 99%
“…Traditionally, it is considered that wear resistance of the coatings just depends on the hardness but nevertheless, elastic modulus also plays a vital contribution in the wear characteristics. [28]. The modulus of elasticity of the G17 piston ring is 110-140 GPa [29], whereas the modulus of elasticity at the complex chromium alloyed grey iron is 154-196 GPa according to DIN 1695 [27].…”
Section: Methodology Applied In Analysing the Chemical Composition Ofmentioning
confidence: 99%
“…It has been reported that even binary coatings like TiN can mitigate the fuel and energy consumption by applying it to the sliding parts of the engine. 310 Therefore, it would be useful to apply other ternary coatings like TiAlN, TiCN, TiSiN, TiCuN, TiMoN, TiCrN, TiZrN, and TiBN on the cylinder liner, piston rings, bearings, gears, and other mechanical components in order to enhance the performance and life of these components, used in automotive and aerospace industry.…”
Section: Applications Of Ternary Nitride Coatingsmentioning
confidence: 99%